PENGELOLAAN PRAKTIK KERJA INDUSTRI - Nanik Susana (Manajer Pendididikan, 2016)
The purpose of the research is to describe the plan, realization and evaluation of industrial working practice at Public Vokational High School Number 1 Ketahun. The method used desriptive qualitative. Subject of this research were headmaster, vice head master, teacher, students and industry instructours. The data collection technique was document, interview and quetioners. The results of the research show that : (1) the plan of industrial working practice in general has followed the guidelines, (2) the realization of industrial working practice in general has followed the planes, (3) the evaluation of industrial working practice the meeting was donethrough between the teachers, commitee and head master.Keywords: management, industrial working practice